Revue de Littérature Comparée: tomo 24 (1950), tomo 25 (1951), tomo 26 (1952), tomo 27 (1953), tomo 28 (1954). - Speratti-Piñero, Emma Susana; Alatorre, Antonio (El Colegio de México, 1962)
Se reseñó el libro: Revue de Littérature Comparée: tomo 24 (1950), tomo 25 (1951), tomo 26 (1952), tomo 27 (1953), tomo 28 (1954).